PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PENERAPAN SAK EMKM TERHADAP KUALITAS LAPORAN KEUANGAN: (Studi Pada UMKM di Dinas Tenaga Kerja Koperasi dan UMKM Kabupaten Bone Bolango) - Makalalag, Nabila; Yusuf, Nilawaty; Lukum, Amir (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The significant increase in MSMEs in Bone Bolango Regency, from 8,172 units in 2021 to 14,600 units in 2024, reflects tremendous economic potential. However, only 1,830 units have achieved financial independence by separating business and personal finances. The main challenge faced is the limitation in preparing financial reports per Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), which affects the quality of financial information for strategic decision-making. This study aims to analyze the impact of human resource quality in implementing SAK EMKM on the quality of MSME financial reports at the Manpower, Cooperatives, and MSME Office in Bone Bolango Regency.Methods: This research method uses a quantitative approach with a causal design, analyzing 95 respondents from independent MSMEs. Respondents were selected through purposive sampling using the Slovin formula with a 10% error rate. The data analysis method used was Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software to assess the outer and inner models, and to test the hypotheses using the bootstrap technique at a 5% significance level.Results: The results showed that human resource quality positively and significantly affects financial report quality, with a path coefficient of 0.476 and a t-statistic of 4.616 (p<0.05). Meanwhile, the implementation of SAK EMKM also showed a positive and significant effect, with a path coefficient of 0.500 and a t-statistic of 4.907 (p<0.05). Together, these two independent variables explained 89.8% of the variation in MSME financial report quality, indicating excellent predictive power of the model. This study confirms the relevance of Human Capital Theory in the context of MSME accounting and recommends developing accounting training programs in accordance with SAK EMKM and improving the technical capabilities of MSMEs to improve financial report quality. Keywords: Financial Report Quality, Human Resource Quality, SAK EMKM, MSMES